2015
DOI: 10.1002/2015jb012210
|View full text |Cite
|
Sign up to set email alerts
|

The frequency dependence and locations of short‐period microseisms generated in the Southern Ocean and West Pacific

Abstract: The origin of the microseismic wavefield is associated with deep ocean and coastal regions where, under certain conditions, ocean waves can excite seismic waves that propagate as surface and body waves. Given that the characteristics of seismic signals generally vary with frequency, here we explore the frequency‐ and azimuth‐dependent properties of microseisms recorded at a medium aperture (25 km) array in Australia. We examine the frequency‐dependent properties of the wavefield, and its temporal variation, ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
52
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 39 publications
(57 citation statements)
references
References 44 publications
5
52
0
Order By: Relevance
“…This can be achieved by using backprojection grid spacing finer than the 400 km used here, and by focusing the array beams with travel time corrections computed from 3D mantle velocity models or with empirical travel time corrections derived from earthquakes near microseism source regions. Using data from a more permanent, non-rolling array with aperture similar to or larger than WTA would also lead to better locations, as might a multi-array backprojection location approach (e.g., Roessler et al, 2010;Pyle et al, 2015;Zhang et al, 2016) and new, sophisticated methods of deconvolving array response functions such as CLEAN-PSF (Gal et al, 2016).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This can be achieved by using backprojection grid spacing finer than the 400 km used here, and by focusing the array beams with travel time corrections computed from 3D mantle velocity models or with empirical travel time corrections derived from earthquakes near microseism source regions. Using data from a more permanent, non-rolling array with aperture similar to or larger than WTA would also lead to better locations, as might a multi-array backprojection location approach (e.g., Roessler et al, 2010;Pyle et al, 2015;Zhang et al, 2016) and new, sophisticated methods of deconvolving array response functions such as CLEAN-PSF (Gal et al, 2016).…”
Section: Discussionmentioning
confidence: 98%
“…To verify these results, we use a new implementation of a conventional three-component f-k (frequency-wavenumber) method (Gal et al, 2016), which is partly based on the work of Wagner (1996). In contrast to backprojection, this method implicitly assumes plane wave propagation across the array and does not rely on a reference velocity model.…”
Section: Example P Sv and Sh Observationsmentioning
confidence: 96%
“…Previously developed localization methods for ambient sources include spectral analysis (e.g., Anthony et al, ; Bromirski, ; Bromirski & Duennebier, ), polarization analysis (e.g., Chevrot et al, ; Schimmel et al, ; Schulte‐Pelkum et al, ), cross correlation‐based imaging (e.g., Ermert et al, ; Stehly et al, ; Tian & Ritzwoller, ; Yang & Ritzwoller, ), beamforming (e.g., Behr et al, ; Gal et al, ; Gerstoft & Tanimoto, ; Juretzek & Hadziioannou, ; Kurrle & Widmer‐Schnidrig, ; Landès et al, ; Reading et al, ; Rhie & Romanowicz, ), migration of cross‐correlation signals (Brzak et al, ; Dales et al, ; Retailleau et al, ), grid searches for fitting particular observables (Gaudot et al, ; Rhie & Romanowicz, ; Shapiro et al, ), and inversion based on simplified plane‐wave models of noise cross correlations (Harmon et al, ; Lehujeur et al, ; Sadeghisorkhani et al, ; Yao & van der Hilst, ). Nishida and Fukao () inverted for the seasonal source of the Earth's hum using a model of cross correlations based on normal modes and a spherically symmetric Earth model.…”
Section: Introductionmentioning
confidence: 99%
“…SchultePelkum et al 2004;Gerstoft et al 2006;Koper & de Foy 2008;Zhang et al 2010a,b;Davy et al 2014). Gal et al (2015) further showed that P waves recorded in Australia are mostly generated close to the coast at periods shorter than 2 s and in deep water at longer periods.…”
Section: Introductionmentioning
confidence: 99%